Assessing Moral Concepts - Masoud Azarbayejani (اخلاق وحیانی, 2012)
This paper aims at assessing moral concepts and investigating scientific and practical approaches to measure moral concepts and values through comparative analysis and psychological & psychiatric approach. Various chapters on research literature, the possibility and necessity of assessing moral concepts, table of symptoms, categorization, scaling and some practical examples are presented in this article. Some of the findings are as follows: the assessing and measuring of moral concepts through experimental psychology & psychiatry models which is possible and attainable. By applying the approach used in etiology and symptomatology in a mental disorder, we can present a new categorization of the moral vices and virtues in this regard. The highest level in assessing moral concepts is defining scales and tests. Some of the Western examples are as follows: Forgiveness Scale, Christian Ethics Test, Distributive Justice Scale and some of the Iranian ones are: Modesty, Patience, Cheerfulness, Jealousy and Wisdom Scales. Based on the existing principles, methodologies & samples, we are able to assess the same methodology for moral concepts to measure other values and concepts as well.